Popular media of the Vietnamese diaspora - Cunningham, Stuart (Javnost (Ljubljana), 1999)
The concept of 'diaspora' can be usefully applied to understanding many of the major population movements this century and to the accompanying complex processes of the maintenance and negotiation of cultural identity. The Vietnamese diaspora is arguably unique because of its historical roots in refugee-exile circumstances. Originally refugees and only lately immigrants, the Vietnamese peoples in the Western world are acutely aware of the conflicting loyalties to their original cultures and the demands of adapting to their new host cultures. In analysing the cultural and media environment inthe Vietnamese diaspora, the article identifies three cultural positions within these communities: the felt need to maintain pre-revolutionary Vietnamese heritage and traditions, to find a negotiated place within a more mainstreamed culture, or to engage in the formation of distinct hybrid identities centering around dominant Western popular cultural forms. Although the Vietnamese audio-visual media industry is very small and of negligible export dynamic, most overseas Vietnamese ultimately reject the output of the 'homeland' as fatally compromised through production under a Communist regime. The article concludes that the media consumed by overseas Vietnamese, rather than resolving these conflicts, tend rather to 'stage' them, give them voice and manage them in a productive tension.
Keywords: Vietnamci; etnične skupine; emigranti; kulturna identiteta; communication medium; mediji; množični mediji; mass media; množične komunikacije